Nutrition: central practice in patient care - Karaboue, Karidia (Progress in Nutrition, 2023)
This paper aims to examine an aspect that shapes everyone’s everyday life, namely nutrition, but from a particular perspective, how its role in treatment is shaped. With all its symbolic correlates and meanings, nutrition plays a central role for humans not only physiologically, but also culturally, morally, identitatively and socio-relatively, as well as within the therapeutic doctor-patient relationship. From a biological and physiological point of view, nutritional status is a fundamental factor for a person’s state of health, homeostasis and immune function, and thus for the ability to cope with stress and disease situations, as it is one of the basic human needs. Food is not only of fundamental importance for the human state of health from a nutritional and metabolic point of view, but also the symbolic means par excellence. Therefore, it is a fundamental aspect to consider, as it represents a mediating element in care to create moments of interaction with the patient, to preserve their residual potential and to promote a sense of normality even in illness.